Reversible Watermarking Using Statistical Information. (26th April 2010) - Mahmoudi Aznaveh Mahmoudi Aznaveh, Ahmad Ahmad; Torkamani-Azar Torkamani-Azar, Farah Farah; Mansouri Mansouri, Azadeh Azadeh; Kurugollu Kurugollu, Fatih Fatih
Abstract : In most reversible watermarking methods, a compressed location map is exploited in order to ensure reversibility. Besides, in some methods, a header containing critical information is appended to the payload for the extraction and recovery process. Such schemes have a highly fragile nature; that is, changing a single bit in watermarked data may prohibit recovery of the original host as well as the embedded watermark. In this paper, we propose a new scheme in which utilizing a compressed location map is completely removed. In addition, the amount of auxiliary data is decreased by employing the adjacent pixels information. Therefore, in addition to quality improvement, independent authentication of different regions of a watermarked image is possible.